Sire Evaluation Based on First Lactation Production Efficiency Traits in Murrah Buffaloes - Chakraborty, D.; Dhaka, S.S. (Journal of Buffalo Science, 2020)
The present investigation was undertaken on data of Murrah buffaloes from Buffalo Research Centre (BRC), Chaudhary Charan Singh Haryana Agricultural University, Hisar distributed over 20 years (1987 to 2006). The sire effects and ranks of 38 sires were estimated on the basis of their daughters’ performance. The progeny group size of the sires ranged from 3 to 17. The sires were evaluated for the different first lactation production efficiency traits, viz. first lactation milk yield (FLMY), first lactation peak yield (FPY), persistency of first lactation milk yield (P), average yield per day of lactation (MY/FLL), milk yield per day of first calving interval (MCI) and milk yield per day of age at second calving (MSC). Sire's breeding values were estimated by the best linear unbiased procedure (BLUP). The estimated breeding values (EBV) for FLMY, FPY, P, MY/FLL, MCI and MSC ranged from –288.42 to 362.20 kg; -1.44 to 4.36 kg; -14.72 to 21.09; –0.44 to 0.63 kg/day; -0.40 to 0.52 kg and -0.09 to 0.16 kg, respectively. FLMY had high and significant product-moment and rank correlations with all other traits. The highest product-moment and rank correlations were obtained between FLMY and MSC to the tune of 0.863±0.043 and 0.835±0.050, respectively. The results indicated that sire coding 33 was the best and can be used for future breeding purpose.